2020
DOI: 10.21037/jtd-20-1241
|View full text |Cite
|
Sign up to set email alerts
|

Extended sleeve-lobectomy for centrally located locally advanced non-small cell lung cancer is a feasible approach to avoid pneumonectomy

Abstract: Backgrounds:The aim of this study was to report our Institutional experience with extended sleeve lobectomy (ESL) in centrally located non-small cell lung cancer (NSCLC), focusing on technical details, post-operative results, recurrence and survival, to determine whether ESL can be accepted as a favorable alternative procedure to pneumonectomy (PN). Methods: Twenty-two consecutive patients undergoing ESL for centrally located tumors from January 2014 to June 2019 were prospectively enrolled. Results: Six (27.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…Lobectomy and lymph node dissection are the standard treatment approaches for early-stage NSCLC. However, this finding is not consistent with the minimally invasive concept of achieving better outcomes with less trauma [ 8 ]. In recent years, segmentectomy has been used to treat early-stage NSCLC.…”
Section: Discussionmentioning
confidence: 73%
“…Lobectomy and lymph node dissection are the standard treatment approaches for early-stage NSCLC. However, this finding is not consistent with the minimally invasive concept of achieving better outcomes with less trauma [ 8 ]. In recent years, segmentectomy has been used to treat early-stage NSCLC.…”
Section: Discussionmentioning
confidence: 73%
“…The characteristics of the incorporated studies are demonstrated in Table 1. From the 126 articles that were retrieved originally, nine studies [4,[10][11][12][13][14][15][16][17] were included in the qualitative and seven in the quantitative analysis [10][11][12][13][14][15][16]. The level of agreement between the reviewers was "almost perfect" (kappa = 0.844; 95% CI: 0.672, 1.000).…”
Section: Search Strategy and Patient Demographicsmentioning
confidence: 99%
“…The level of agreement between the reviewers was "almost perfect" (kappa = 0.844; 95% CI: 0.672, 1.000). In addition, the study design was prospective in four studies [10,12,15,16] and retrospective in five studies [4,11,13,14,17]. Moreover, the incorporated studies were conducted in Japan [4,11,13,17], France [10], Italy [12,15], Korea [14], and China [16], and were published between 1999 and 2022.…”
Section: Search Strategy and Patient Demographicsmentioning
confidence: 99%
See 2 more Smart Citations